2014
DOI: 10.1111/vru.12223
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Diagnosis—spontaneous Pneumomediastinum Secondary to Primary Pulmonary Pathology in a Dalmatian Dog

Abstract: A 1.5-year-old, 23 kg intact male Dalmatian dog was evaluated for acute respiratory insufficiency without a previous history of trauma or toxic exposition. Imaging revealed pneumomediastinum, pneumothorax, diffuse unstructured interstitial pulmonary pattern, pulmonary interstitial emphysema, and pneumoretroperitoneum. Histopathological evaluation of the lungs revealed perivascular and peribronchial emphysema, mild lymphocytic interstitial pneumonia with atypical proliferation of type II pneumocytes in bronchio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 11 publications
1
35
2
3
Order By: Relevance
“…presence of air in mediastinum or mediastinal emphysema and bilateral pneumothorax, i.e. presence of air in pleural cavities following near drowning It must be noted that in literature several reports, the wider term spontaneous pneumomediastinum, has a more favourable outcome and even more rare compared to secondary pneumomediastinum, has been allowed even when a possible causative factor is identified 1 .…”
Section: Discussion:-mentioning
confidence: 99%
See 2 more Smart Citations
“…presence of air in mediastinum or mediastinal emphysema and bilateral pneumothorax, i.e. presence of air in pleural cavities following near drowning It must be noted that in literature several reports, the wider term spontaneous pneumomediastinum, has a more favourable outcome and even more rare compared to secondary pneumomediastinum, has been allowed even when a possible causative factor is identified 1 .…”
Section: Discussion:-mentioning
confidence: 99%
“…Another possible explanation for pneumomediastinum is, the abnormal increase of pressure in the mediastinum causing air to dissect in between the mediastinal structures, which support the mediastinal organs. A dramatic decrease in intravascular pressure also can create a relative pressure gradient in the perivascular spaces 1 . The air may then dissect to the neck, upper abdomen or the skin via the loose alveolar fat tissue (subcutaneous emphysema) 8 .…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Most affected patients (76%) are male [5]. In addition, several reports of pneumomediastinum in middle-aged patients reported that affected patients had some risk factors [6].…”
Section: Discussionmentioning
confidence: 99%
“…A dramatic decrease in in travascular pressure also can create a relative pressure gradient in the perivascular spaces. The air may then dissect to the neck, upper abdomen or the skin via loose alveolar fat tissue (subcu taneous emphysema) 19) .…”
Section: Conflicts Of Interestmentioning
confidence: 99%